2021
DOI: 10.1186/s12916-021-02103-4
|View full text |Cite
|
Sign up to set email alerts
|

Transmission event of SARS-CoV-2 delta variant reveals multiple vaccine breakthrough infections

Abstract: Background This study aims to identify the causative strain of SARS-CoV-2 in a cluster of vaccine breakthroughs. Vaccine breakthrough by a highly transmissible SARS-CoV-2 strain is a risk to global public health. Methods Nasopharyngeal swabs from suspected vaccine breakthrough cases were tested for SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) by qPCR (quantitative polymerase chain reaction) for Wuhan-Hu1 and alpha variant. Positive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
109
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(117 citation statements)
references
References 18 publications
3
109
0
Order By: Relevance
“…Breakthrough infections occur in individuals with vaccine-or infection-induced SARS-CoV-2 immunity, especially by the circulating Delta strain (41)(42)(43). Such infections may be more frequent or more pathogenic in individuals with low anti-WA1 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Breakthrough infections occur in individuals with vaccine-or infection-induced SARS-CoV-2 immunity, especially by the circulating Delta strain (41)(42)(43). Such infections may be more frequent or more pathogenic in individuals with low anti-WA1 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of an outbreak in the gym showed that the Delta variant was highly transmissible [10]. In addition, the Delta variant had been associated with multiple vaccine breakthrough infections [11].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that the benefits of COVID-19 vaccines outweigh the risks [ 14 ]. The early, broad vaccination coverage in Israel and the UK provided clear evidence that the vaccine reduces severe illness and death [ 15 , 16 , 17 , 18 ], but the extent to which it reduces transmission is not yet confirmed [ 19 , 20 , 21 , 22 ], particularly given the different characteristics of the virus variants. Vaccine hesitancy has declined in many countries, yet coverage still seems to be insufficient to allow a smooth return to “normal” life [ 23 ].…”
Section: Discussionmentioning
confidence: 99%